2014
DOI: 10.1021/pr400952z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Quantitative Analysis of Nitrogen Stress Response inChlamydomonas reinhardtiiUsing Metabolite and Protein Profiling

Abstract: Nitrogen starvation induces a global stress response in microalgae that results in the accumulation of lipids as a potential source of biofuel. Using GC-MS-based metabolite and iTRAQ-labeled protein profiling, we examined and correlated the metabolic and proteomic response of Chlamydomonas reinhardtii under nitrogen stress. Key amino acids and metabolites involved in nitrogen sparing pathways, methyl group transfer reactions, and energy production were decreased in abundance, whereas certain fatty acids, citri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
152
2
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(181 citation statements)
references
References 85 publications
15
152
2
12
Order By: Relevance
“…A similar strategy was recently discussed for adaptation of southwestern Australia Proteaceae species that grow on extremely low P soils and contain very low levels of ribosomes in their young leaves (Sulpice et al, 2013). The resulting switch from wellbalanced (mixotrophic) energy production between photosynthesis and respiration in N-replete conditions to mainly mitochondrial energy generation in N-starved C. reinhardtii (Figures 2 and 3; Plumley and Schmidt, 1989;Peltier and Schmidt, 1991;Bulté and Wollman, 1992;Wang et al, 2009;Longworth et al, 2012;Wase et al, 2014;Wei et al, 2014) allows extraction of N from abundant and N-rich chloroplast proteins, like the photosystems or CalvinBenson cycle enzymes (especially Rubisco). It is accompanied by a particular large decrease of plastid ribosomal proteins compared with cytosolic ribosomal proteins; this presumably reflects the fact that the former are almost exclusively involved in synthesis of proteins in the thylakoid complexes and the large subunit of Rubisco, whereas the synthesis of photosynthesis proteins is only one of many tasks performed by the latter.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A similar strategy was recently discussed for adaptation of southwestern Australia Proteaceae species that grow on extremely low P soils and contain very low levels of ribosomes in their young leaves (Sulpice et al, 2013). The resulting switch from wellbalanced (mixotrophic) energy production between photosynthesis and respiration in N-replete conditions to mainly mitochondrial energy generation in N-starved C. reinhardtii (Figures 2 and 3; Plumley and Schmidt, 1989;Peltier and Schmidt, 1991;Bulté and Wollman, 1992;Wang et al, 2009;Longworth et al, 2012;Wase et al, 2014;Wei et al, 2014) allows extraction of N from abundant and N-rich chloroplast proteins, like the photosystems or CalvinBenson cycle enzymes (especially Rubisco). It is accompanied by a particular large decrease of plastid ribosomal proteins compared with cytosolic ribosomal proteins; this presumably reflects the fact that the former are almost exclusively involved in synthesis of proteins in the thylakoid complexes and the large subunit of Rubisco, whereas the synthesis of photosynthesis proteins is only one of many tasks performed by the latter.…”
Section: Discussionmentioning
confidence: 83%
“…Hence, there is considerable interest in nitrogen use efficiency (NUE) in plants, and now in algae, because of growing interest in biotechnological applications (Scott et al, 2010;Xu et al, 2012;Wase et al, 2014). Molecular analyses of the responses to N nutrition have been investigated and detailed for decades, including (especially in C. reinhardtii) the complex circuitry of ammonium versus nitrate utilization (Fernandez and Galvan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…It could be shown that in this case the glyoxylate pathway, as well as activity of acetyl-CoA synthetase was down regulated [44,45]. Thus, Chlamydomonas reinhardtii is using a second pathway via acetate kinase and phosphate acetyltransferase for acetate assimilation, thereby maintaining basic cellular functions and providing energy [45]. Excess carbon can be directly used for fatty acid biosynthesis [44].…”
Section: Biology Of Vfa Utilization;mentioning
confidence: 97%
“…Another important aspect during N-deprivation is the reduced activity of isocitrate dehydrogenase resulting in an increase of citrate levels. Citrate can be converted into oxaloacetate and acetyl-CoA via ATP citrate lyase providing further acetyl-CoA for fatty acid biosynthesis [45].…”
Section: Biology Of Vfa Utilization;mentioning
confidence: 99%